Craniocerebral Hypothermia Stimulates Reactions of Limited Proteolysis in Rat Tissues - Lomako, Viktoriya V.; Shylo, Aleksandr V.; Babijchuk, Georgiy A.; Samokhina, Lyubov M. (Problems of Cryobiology and Cryomedicine, 2016)
The effect of moderate craniocerebral hypothermia (CCH) (32Â°C) on total proteinase activity (TPA), the activity of non-trypsin-like proteinases (NTLP) and their inhibitors (a-1-proteinase inhibitor (a-1-PI) and a-2-macroglobulin (a-2-MG) in the tissue samples of CNS (brain cortex, hypothalamus, cerebellum), peripheral organs (heart, lungs, liver, kidneys) and serum blood in rats was studied. In all the samples studied a sharp increase in the TPA (by one to two orders) and the NTLP activity (in several times) under CCH were observed. At the same time, against the background of constant a-1-PI activity the dynamics of the a-2-MG activity were multidirectional and tissue-specific: it was increased in blood serum, hypothalamus and heart, decreased in kidneys and cerebellum, and did not change in other tissues. Twenty four hoursÂ after the CCH application, the TPA remained at the same high activity level, the NTLP activity returned to baseline levels in the most samples, the activity of a-1-PI decreased only in the brain cortex and hypothalamus; the aâ€‘2â€‘MG activity decreased in hypothalamus, cerebellum and kidneys, increased in liver and heart and returned to the baseline levels in other samples. The sharp proteinases activation, shift of the dynamic balance between enzymes and their inhibitors under CCH and in the recovery phase may indicate crucial changes in the orgamism systems aimed atÂ implementation ofÂ protective and therapeutic mechanisms. Â Probl. Cryobiol. Cryomed. 2016; 26(3): 238â€“248